Synthesis of pure nano Cr2O3 from chromite ore by a novel method and investigation of its composites with bentonite for their photocatalytic properties - Khatamian, Maasoumeh; Dastar, Elham; Fazli-Shokouhi, Sara; Hosseini Nami, Shamin (Journal of the Iranian Chemical Society, 2023)
In the present study, nano Cr 2 O 3 was prepared with a novel method from chromite ore. In this method, K 2 Cr 2 O 7 was prepared by alkaline melting of chromite ore. Then, the precursor complex K 3 [Cr(C 2 O 4 ) 3 ] was prepared using potassium dichromate obtained from chromite ore and Merck Co. for comparing their purity. Therefore, two types of nano (Cr 2 O 3 ) M or ch (M = Merck, ch = chromite ore) were prepared by destructing the gel contained K 3 [Cr(C 2 O 4 ) 3 ] and starch as an eco-friendly material for controlling the size and morphology of the nanoparticles. So, these nanoparticles were characterized by XRD, FESEM, and EDX. The ball-milled bentonite (B) was used for the preparation of (Cr 2 O 3 (n% = 30, 50, and 70%)/B) ch and (Cr 2 O 3 (n% = 30, 50%)/B) M nanocomposites. The XRD and FESEM of (Cr 2 O 3 (n%)/B) ch and (Cr 2 O 3 (n%)/B) M are the same. So, the (Cr 2 O 3 (n%)/B) ch nanocomposites were just used for further investigations, such as photocatalytic properties, and analysed by other techniques, including FTIR and DRS. The (Cr 2 O 3 (30%)/B) ch showed the highest degradation property, 69% after 240 min, among other prepared nanocomposites to destroy methylene blue with 10 ppm concentration at pH = 10 under UV irradiation. Also, the (Cr 2 O 3 (30%)/B) ch could degrade methyl orange with 10 ppm concentration at pH = 7 up to 74% after 240 min. Nano Cr 2 O 3 and bare bentonite efficiency for methylene blue and methyl orange degradation were lower (< 30%) under the same conditions.